Confinement effect in two-phase closed thermosyphon - Kang, Sukkyung; Lee, Jungho (International Communications in Heat and Mass Transfer, 2025)
In recent years, space and cost constraints, in addition to the necessity to recover trace amounts of waste heat, have led to the miniaturization of heat pipe heat exchangers for waste heat recovery, resulting in the utilization of small-diameter two-phase closed thermosyphon (TPCT). A TPCT with a small dimension has a different nature of internal two-phase flow and heat transfer than a larger one, known as the “Confinement effect.” Despite the recent utilization of compact TPCT, the working mechanism of small-diameter TPCT is not clearly understood. In the present work, the confinement effect of TPCT, particularly two-phase flow and heat transfer characteristics, was experimentally explored for various inner diameters (5, 10, 15, 20, and 25 mm) and working fluids (water, acetone, ethanol, and the HFE-7000), using the thermosyphon devices that can simultaneously measure flow patterns and thermal performance. For the thermal performance by confinement, the higher the figure of merit (FOM) and the larger the inner diameter, the better the thermal performance. Finally, we presented the criteria for the stable operation of TPCT; the results showed that it could work stably with minimal influence of confinement at both confinement number (Co) and Froude number (Fr) below 0.3.
Keywords: Confinement effects; Diameter twos; Flow and heat transfer; Inner diameters; Space constraints; Thermal Performance; Two phases flow; Two-phase closed thermosiphon; Two-phase closed thermosyphon; Working fluid; Confinement effect; Inner diameter; Two-phase closed thermosyphon (TPCT); Working fluid